Perancangan Motif Batik Rumah Gadang Dalam Busana Kasual - Nifha Sartika; I Made Sukanadi; Aruman A (Style : Journal of Fashion Design, 2021)
Rumah Gadang, known by the Minangkabau people as the Bagonjong house or the Baanjuang house, is a West Sumatran traditional house which is one of Indonesia's distinctive architectural heritages which is still being preserved. One way to preserve it is to animate it as a source of inspiration in the creation of a work of= art. The purpose of this study is to visualize the shape of Rumah Gadang into a batik motif in casual clothing. This applied research uses the method of creation ranging from observation of data in the field to the realization of the work. This creation research resulted in seven design works and three works that were realized in the form of clothing. The characteristics of the work are made different, with a typical concept of Casual clothing.